Degradation of palm kernel cake by extracellular crude enzyme of SP1 isolate from Poring hot spring, Sabah, Malaysia - Nurshafrina Aida, Yahya; Bak Zaibah, Fazal; Rafida, Razali; Zarina, Amin; Cahyo, Budiman (Journal of Sichuan University., 2022)
This study aims to confirm the ability of the SP1 isolate from Poring hot spring, Sabah, Malaysia, to degrade palm kernel cake (PKC). To achieve this, crude enzymes (CE) of this isolate was collected from cell-free supernatant following a 24-hour incubation at 50°C. The CE's protein content was determined to be 92.20 ± 5.74 mg/L culture. Further hydrolysis of PKC by CE indicated a reduction in both cellulose and hemicellulose contents of PKC, up to a 6-hour reaction time. This result was accompanied by an increase in reducing sugar concentration, confirming that CE degrades hemicellulose and cellulose to produce reducing sugars. It indicates that the CE contained a mixture of enzymes that worked on both substrates. The hydrolysis of PKC by CE of SP1 isolate was optimal at 60°C and pH 6.0. Additionally, the activity was enhanced by Tween 80 up to 0.2%. These findings suggest that the SP1 isolate has potential for use in PKC degradation. However, further studies on the enzymatic degradation process using purified enzymes are needed.